Synthetic Sacks as Reinforced Fibers in the Thermosetting Composites - Hussien, Mukheled A.; Abass, Falak O.; Abass, Raghad O. (Al-Khwarizmi Engineering Journal, 2010)
This study was carried out to investigate the preparation of thermosetting polymeric blend consisting of three adhesive types, namely: epoxy, polyvinyl formal (PVF) and unsaturated polyester. Both of epoxy and PVF were used as a matrix-binder at fixed weight. Whilst unsaturated polyester was used at different weights and added to the matrix so as to produce prepared epoxy-PVF-unsaturated polyester blend. Several experiments were performed at different operating conditions, mixing speed and time at room temperature to identify the most favorable operating conditions. The optimum mixing speed and mixing time for the prepared blend were 500rpm and 5 minutes respectively.      Solid wastes-synthetic sack fibers from high volume, low cost, renewable fiber sources have been used as environmentally friendly alternatives to reinforcing fibers in composites. Many mechanical and thermal tests were carried out of the prepared blend at different weighted ratios. The optimum weighted ratio of the prepared blend for the untreated samples was characterized by the hardness and bending deflection properties and it was 0.40w/w, while for impact strength and thermal conductivity properties was 0.20w/w respectively. At these optimum weighted ratios of untreated samples with sack fibers, the maximum values of hardness and impact strength properties were 95 shore and 2.25J/cm2 respectively. On the other hand, the minimum bending deflection and thermal conductivity properties values were found to be 4mm and 0.01094W/cm.oC respectively. They showed the best bonding forces and physical interaction between two concentrations of matrix and unsaturated polyester adhesives.      Treated samples of sack fibers reinforced composites at their optimum weighted ratio showed better fiber-matrix interaction as observed from the experimental results leading to enhance and improve the mechanical (hardness, impact strength, and bending deflection) and thermal (thermal conductivity) properties when compared to the untreated sample. These improvements in treated samples with two layers of sack fibers were predominant.